How Do The Environmental Aspects Affect The Oil Drilling And Extraction Sector? Evidence From Firm-Level Data - Amr Hosny, Nadine (AUC Knowledge Fountain, 2023)
There will and always be a tradeoff between achieving profitability and maintaining sustainability. This complex problem is especially portrayed in the Oil sector. MENA region countries dominate more than half of the Oil reserves globally. Therefore and due to their dominance, such oil firms may suffer from several adverse consequences from their oil drilling and extraction activities. Accordingly, the main objective of the thesis is to examine the impact of the changes in environmental conditions on the financial performance of selected oil drilling and extraction firms. The selected countries that were chosen are: Egypt, Morocco, Tunisia & Gabon. The results surprisingly concluded that the rise in Carbon Dioxide emissions & Annual Average Temperature had a negative impact on the Market Value of the selected firms.